Faktor Penentu Ketepatan Smash Klub Bolavoli Mars 76 Kota Kediri Tahun 2023 - Rozi, Fathur; Junaidi, Slamet; Muharram, Nur Ahmad (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The purpose of this study was to determine the correlation of leg muscle strength with smash accuracy, to determine the correlation of hand eye coordination with smash accuracy, to determine the correlation of arm muscle strength with smash accuracy and to determine the correlation of leg muscle strength, hand eye coordination and arm muscle strength with smash accuracy in volleyball game at the Mars 76 Volleyball Club Kediri City in 2023. In this study the approach used was a quantitative approach, researchers used a correlational method. The population and sample in this study were 15 women's volleyball athletes from Mars 76. Data collection techniques in research are test and measurement techniques. Based on the results of the study, it showed that there was a significant relationship between leg muscle strength and smash accuracy, with rx1.y = 3.502 > r(0.05)(15) = 0.382, there was a significant relationship between hand eye coordination and smash accuracy, with rx2.y = 3.433 > r(0.05)(15) = 0.472 and there is a significant relationship between arm muscle strength and smash accuracy, with rx3.y = 1.851 > r(0.05)(15) = 0.462. From the results of this analysis, the correlation coefficient between leg muscle strength, eye-hand coordination and arm muscle strength was obtained with a smash accuracy of 0.515. The weight test for the correlation coefficient was carried out by consulting the value of F count 4,850 > F table at a significance level of 5% and degrees of freedom 3;15, namely 3,187, and Rx1.x2.x3.y = 0.515 > R(0.05)(15) = 3,187 , means that the correlation coefficient is significant. The hypothesis reads